ChemInform Abstract: Catalytic Asymmetric Conjugate Addition of α‐Fluoro β‐Ketophosphonates to Nitroalkenes in the Presence of Nickel Complexes. Issue 6 (21st January 2016) - Sung, Hyun Ji; Mang, Joo Yang; Kim, Dae Young
Abstract: The reaction of α‐fluoro β‐ketophosphonates (I) with nitroalkenes [(II) or (IV), resp.] affords the corresponding Michael adducts [(III) or (V), resp.] in high yields, high diastereoselectivities and excellent enantioselectivities.